Effects of Mg2+, Fe3+, Mn2+ and Cu2+ Ions on lipid accumulation by cunninghamella bainieri 2A1 - Vidyah Manikan,; Mohd Sahaid Kalil,; Othman Omar,; Abdul Jalil Abdul Kader,; Aidil Abdul Hamid, (Universiti Kebangsaan Malaysia, 2014)
Cunninghamella bainieri 2A1 is an oleaginous fungus whose lipid accumulation profile is significantly influenced by metal ion concentrations in growth medium. Mg2+, Fe3+, Mn2+ and Cu2+ were found to be the important elements affecting lipid accumulation in this fungus. This study employs a statistical method (Response Surface Methodology – RSM) to study the combined effects of Mg2+, Fe3+, Mn2+ and Cu2+ on lipid accumulation of C. baineri 2A1. Cultivation was carried out in 250 mL Erlenmeyer flasks containing 100 mL nitrogen limited medium at 30ºC and 250 rpm agitation for 120 h. A thirty-run central composite design experiment was employed to identify and optimize the significant factors. In addition to Mg2+ and Fe3+ which were shown to have significant effects on lipid accumulation, the interactions between Mg2+ and Cu2+, as well as the effect of Cu2+ in quadratic terms were also found to have significant effect on the process (p<0.05). The highest amount of lipid obtained in this study was 39% g/g biomass with optimal levels of Mg2+, Fe3+ and Cu2+ at 5.00, 0.017 and 0.0005 g/L, respectively, while Mn2+ was omitted. A 32% increment in lipid yield was recorded, where the lipid content increased to 38%, compared to initial yield of 29% g/g biomass prior to optimization. In conclusion, Mg2+ and Fe3+ have significant positive effect on the lipid accumulation of this fungus, whereas Mn2+ and Cu2+ exert negative effects in combination.